A study comparing patient satisfaction and retention of CAD/CAM milled complete dentures and 3D printed CAD/CAM complete dentures versus conventional complete dentures: a randomized clinical trial - Mohamed Abo Heikal, Mohamed; Abdel Nabi , Nouran; Wagdy Elkerdawy, Maha (Brazilian Dental Science, 2022)
Objective: To compare the three different methods of complete denture fabrication assessing patient satisfaction and retention after insertion for six months’ follow-up period. Material and Methods: The study was conducted in the Prosthodontic Department where a total of forty-eight patients were recruited from the outpatient clinics fulfilling the inclusion criteria. This study was designed as a randomized controlled clinical trial. All patients followed the steps of complete denture construction till jaw relation record. Then, all eligible patients were randomized to intervention and control groups. For intervention groups digital scanning, designing, manufacturing of complete dentures was done; 3D printing for first and milling for second intervention. For the comparator group, complete dentures were manufactured the conventional way. After 2 weeks of delivery of the dentures, patients received a patient satisfaction questionnaire, retention was measured by retention force gauge. Both readings were also recorded after 3 months and at 6 months. The mean and standard deviation values were calculated for each group in each test. The significance level was set at P < 0.05. Results: No statistical difference was found in terms of patient satisfaction and retention between the three groups at different time intervals. Conclusion: The manufacturing technique seemed to have no influence on patient satisfaction and retention with milled showing the least results. KEYWORDS Computer-aided design; Denture, Complete; Denture retention; Patient satisfaction; Printing, Three-dimensional